2008
DOI: 10.1590/s1809-29502008000100014
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do exercício físico durante a hemodiálise em indivíduos com insuficiência renal crônica: uma revisão

Abstract: FISIOTERAPIA E PESQUISA 2008; 15(1): 86-91 RESUMO: As principais alterações observadas em indivíduos com insuficiência renal crônica são anemia, hipertensão arterial sistêmica e atrofia muscular, que levam à baixa capacidade aeróbica e perda de força muscular. Assim, parte do tratamento desses indivíduos consiste em programas de exercício físico. O objetivo desta revisão da literatura foi documentar os efeitos agudos e as adaptações crônicas, cardiovasculares e musculares em indivíduos no estágio final da doen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 25 publications
(37 reference statements)
1
10
0
15
Order By: Relevance
“…6 Some studies have reported that physical exercise training programs have modified morbidity and survival of azotemic patients, causing metabolic, physiological, and psychological benefits. 1,8,9,11 When properly supervised, exercises performed during HD are indicated and safe for those patients, 1,8,9 although they have not become routine in dialysis centers. 11 Thus, the present study aimed at assessing the results of a physical therapy intervention on the respiratory muscle function, grip strength, and QOL of patients undergoing HD.…”
Section: Repercussion Of An Intradialytic Physical Therapy Protocolmentioning
confidence: 99%
See 4 more Smart Citations
“…6 Some studies have reported that physical exercise training programs have modified morbidity and survival of azotemic patients, causing metabolic, physiological, and psychological benefits. 1,8,9,11 When properly supervised, exercises performed during HD are indicated and safe for those patients, 1,8,9 although they have not become routine in dialysis centers. 11 Thus, the present study aimed at assessing the results of a physical therapy intervention on the respiratory muscle function, grip strength, and QOL of patients undergoing HD.…”
Section: Repercussion Of An Intradialytic Physical Therapy Protocolmentioning
confidence: 99%
“…Repercussion of an intradialytic physical therapy protocol et al (2008) 8 has evidenced an improvement in the "physical functioning" and "mental health" domains of SF-36 in the experimental group, which underwent a physical exercise program comprising aerobic and muscle strength training for 16 weeks, as compared with the control group. Soares et al (2007) 4 have recommended an active exercise training for lower and upper limbs, consisting of 24 sessions, three times per week, similar to the protocol of the present study.…”
Section: Quality Of Lifementioning
confidence: 99%
See 3 more Smart Citations